Microvessel density and vascular endothelial growth factor receptors in breast carcinoma under the influence of rapamycin and platelet factor 4 - Muhammad Shahidan Muhammad Sakri; Wan Faiziah Wan Abdul Rahman; Tengku Ahmad Damitri Al-Astani Tengku Din; Fauziah Mohd Idris; Hasnan Jaafar (Wolters Kluwer Medknow Publications, 2020)
Background: Vascular endothelial growth factor receptors (VEGFRs) are major endothelial growth factor receptors that influence the growth of a tumor. Microvessel density ( MVD) is the quantification method of various aspects of tumor vasculature that indicates angiogenic activity. This study aims to analyze the correlation between MVD to the expression of VEGFRs on breast cancer tissue. Materials and Method: A total of 60 N-methyl-N-nitrosourea (MNU)-induced breast carcinomas in rats were suppressed by using antiangiogenic drugs. The rats were then sacrificed, and the tumor was fixed in 10% formalin, paraffin embedded, and immunohistochemistry stained using VEGFRs and CD34. Result: One-way ANOVA test showed a significant difference in all markers that have been used (P < 0.05) on MNU-breast tumor treated with rapamycin (M= 90.1664, SD= 7.4487), PF4 (M= 93.7946, SD= 7.1303) and rapamycin + PF4 (M= 93.6990, SD= 1.8432). We obtained a significant reduction of MVD count on breast carcinoma for rapamycin group (M= 25.6786, SD= 9.7075) and rapamycin + PF4 group (M= 30.5250, SD= 13.6928) while PF4 group (M=47.7985, SD=4.8892) showed slightly increase compared to control (M= 45.1875, SD= 4.4786). There was a moderately strong, positive correlation between angiogenic markers; Flt-1 (r= 0.544, n=60, P < 0.005) and Flt-4 (r= 0.555, n= 60, P < 0.005) while Flk-1 (r= 0.797, n= 60, P < 0.005) showed a strong, positive correlation with MVD. Conclusion: MVD was strongly correlated to the VEGFRs expression on breast carcinoma.